Critical Theory, Democracy, and the Challenge of Neoliberalism - Caterino, Brian; Hansen, Phillip (University of Toronto Press, 2023)
With a few exceptions, critical theorists have been late to provide a comprehensive diagnosis of neoliberalism comparable in scope to their extensive analyses of advanced welfare state capitalism. Instead, the main lines of critical theory have focused on questions of international justice which, while no doubt significant, restrict the scope of critical theory by deemphasizing linkages to larger political and economic conditions. Providing a critique of the Frankfurt School, Brian Caterino and Phillip Hansen move beyond its foundations, and call for a rethinking of the bases of critical theory as a practical, freedom-creating project. Outlining a resurgence of neoliberalism, the authors encourage a fresh, nuanced analysis that elucidates its political and economic structures and demonstrates the threats to freedom and democracy that neoliberalism poses. They propose the reformulation of a radical democratic alternative to neoliberalism, one that critically addresses its limitations while promoting an enhancement of communicative and social freedom.